Impact of the serum‐ and glucocorticoid‐inducible kinase 1 on platelet dense granule biogenesis and secretion. (12th June 2015) - Walker, B.; Schmid, E.; Russo, A.; Schmidt, E.‐M.; Burk, O.; Münzer, P.; Velic, A.; Macek, B.; Schaller, M.; Schwab, M.; Seabra, M. C.; Gawaz, M.; et al.
Summary Background Platelet secretion is critical to development of acute thrombotic occlusion. Platelet dense granules contain a variety of important hemostatically active substances. Nevertheless, biogenesis of platelet granules is poorly understood. Objectives Serum‐ and glucocorticoid‐inducible kinase 1 (SGK1) has been shown to be highly expressed in platelets and megakaryocytes, but its role in the regulation of platelet granule biogenesis and its impact on thrombosis has not been investigated so far. Methods and Results Electron microscopy analysis of the platelet ultrastructure revealed a significant reduction in the number and packing of dense granules in platelets lacking SGK1 (sgk1−/−). In sgk1−/− platelets serotonin content was significantly reduced and activation‐dependent secretion of ATP, serotonin and CD63 significantly impaired. In vivo adhesion after carotis ligation was significantly decreased in platelets lacking SGK1 and occlusive thrombus formation after FeCl3‐induced vascular injury was significantly diminished in sgk1−/− mice. Transcript levels and protein abundance of dense granule biogenesis regulating GTPase Rab27b were significantly reduced in sgk1−/− platelets without affecting Rab27b mRNA stability. In MEG‐01 cells transfection with constitutively active S422DSGK1 but not with inactive K127NSGK1 significantly enhanced Rab27b mRNA levels. Sgk1−/− megakaryocytes show significantly reduced expression of Rab27b and serotonin/CD63 levels compared with sgk1+/+ megakaryocytes. Proteome analysis identified nine further vesicular transport proteins regulated by SGK1, which may have an impact on impaired platelet granule biogenesis in sgk1−/− platelets independent of Rab27b. Conclusions The present observations identify SGK1 as a novel powerful regulator of platelet dense granule biogenesis, platelet secretion and thrombus formation. SGK1 is at least partially effective because it regulates transcription of Rab27b in megakaryocytes.